The Effect of Work Planning and Division of Tasks on the Work Achievement of Employees of the Education and Culture Office of Empat Lawang Regency - Dilia, Dora; Hardiyansyah; Aprini , Nisma (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine and analyze the influence of work planning and task division partially and simultaneously on the work performance of employees of the Empat Lawang Regency Education and Culture Service. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results of the analysis explain that work planning has a significant effect on the work performance of employees of the Empat Lawang Regency Education and Culture Service. The results of the analysis explain that the division of tasks has a significant effect on the work performance of employees of the Empat Lawang Regency Education and Culture Service. The results of the analysis explain that work planning and division of tasks have a significant effect together on the work performance of employees of the Empat Lawang Regency Education and Culture Service.